Mesenchymal Stem Cell as a Successful Therapy for COVID-19 Patient: Systematic Review - Rahmah Qisti Nandina; Kartini Eriani; Cynthia Wahyu Asrizal; Al Azhar (Biosaintifika: Journal of Biology & Biology Education, 2022)
COVID-19 has been declared a pandemic and continues to spread, leading to health and economic problems and economic burdens worldwide. COVID-19 symptoms are similar to the flu and, in severely infected patients, emerge as an acute respiratory syndrome (ARDS), pulmonary fibrosis, edema, and even organ failure. These are due to an imbalanced immune response with a more severe effect than the virus attack. However, no specific medications and treatments are available in dealing with the COVID-19. Hence, mesenchymal stem cell (MSC) treatment is proposed as one therapeutic approach. The MSCs can produce growth factors and immune protective cytokines that could fight viral infection and are proven to help endothelial cell repair. These capabilities are expected to help resist viruses and tissue repair in a patient body. MSC is believed to prevent acute respiratory infections, the most dangerous stage of COVID-19 pathogenesis. In this study, we collect some literature, reviewing and summarizing them so that we believe that MSC could be an approach to cure COVID-19 patients and improve their responses to the virus. This article reviews the use of mesenchymal stem cells as a potential therapy for COVID-19, and this information can also be used as basic information for developing a stem-cell-based therapy, especially for treating COVID-19.